Sandwich antibody-based biosensor system for identification of Mycobacterium tuberculosis complex and nontuberculous mycobacteria. Issue 6 (2nd November 2019) - Chuensirikulchai, Kantinan; Laopajon, Witida; Phunpae, Ponrut; Apiratmateekul, Napaporn; Surinkaew, Sirirat; Tayapiwatana, Chatchai; Pata, Supansa; Kasinrerk, Watchara
ABSTRACT: Mycobacterial infection, leading to pulmonary disease, remains a world health problem. Clinical symptoms of pulmonary disease caused by Mycobacterium tuberculosis complex (MTBC) and nontuberculous mycobacteria (NTM) are very similar. A rapid method for the differentiation of MTBC and NTM infection is essential for appropriate therapy. In this study, we aim to establish an antibody-based biosensor system for the identification of MTBC and NTM infection. Monoclonal antibodies (mAbs) specific for Ag85B proteins of mycobacteria were generated and characterized. The generated anti-Ag85B mAb clones AM85B-5 and AM85B-8 reacted to Ag85B of Mycobacterium spp.; in contrast, clone AM85B-9 specifically reacted to Ag85B of MTBC. By employing the produced mAbs, single and sandwich antibody-based biosensors using bio-layer interferometry were established for determination of Ag85B proteins. The sandwich antibody-based biosensor system was demonstrated to be suitable for detection of Ag85B protein and identification of MTBC and NTM. Using anti-Ag85B mAbs AM85B-8 and AM85B-9 as immobilized antibodies on sensor chips and using mAb AM85B-5 as secondary antibody, the established sandwich antibody-based biosensor could discriminate MTBC and NTM. The developed biosensor system can be used for culture confirmation of mycobacteria and speciation to MTBC and NTM.